A rare case of strontium induced dermatitis in an osteoporotic patient taking an over-the-counter supplement: a case study - Batukbhai, Bhalala Priyank; Pranaya, Rajbhandari; Ribadiya, Fenilkumar Nitinbhai; Zaleski, Henry (International Journal of Research in Medical Sciences, 2025)
Strontium ranelate, a strontium salt, is used in osteoporosis treatment due to its dual mechanism of promoting bone formation and inhibiting resorption. Although it is effective, strict monitoring is recommended because of it adverse reactions particularly related to cardiovascular and cutaneous adverse reactions. We report the case of a 71-year-old woman with a 20-year history of osteoporosis who developed progressive dermatitis and generalized pruritus over 1.5 years. Extensive dermatologic and rheumatologic evaluations, including skin biopsies, were inconclusive. Upon detailed history, the patient disclosed long-term use of an over-the-counter (OTC) vitamin supplement containing strontium citrate. Performed laboratory testing revealed significantly elevated serum strontium levels (124.2 ng/ml; reference: 8.3-34.3). After discontinuation of the supplement, her symptoms gradually resolved without specific treatment. This case highlights strontium toxicity manifesting as cutaneous symptoms, potentially caused by chronic ingestion of OTC strontium. While adverse effects of prescription strontium ranelate are documented, reports of toxicity from non-prescription strontium citrate are rare. The patient’s clinical improvement and declining strontium levels after supplement cessation strongly support the diagnosis. This is a rare and possibly novel case of cutaneous strontium toxicity linked to an OTC supplement. Clinicians should consider strontium toxicity in patients presenting with unexplained dermatitis and a history of osteoporosis, particularly when supplement use is identified. Greater awareness and regulation of strontium-containing OTC products are warranted.